Effect on Sedimentation Behavior and Performance of Irrigation Channel at Waru-Turi Kanan Kediri - Wirosoedarmo, Ruslan; Haji, Alexander Tunggul Sutan; Kristanti, Estin D. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2011)
The objectives of this research were to determine the rate of sedimentation in the primary, secondary, and tertiary channel; to determine channel dimension changes caused by sediment, and the effect of sedimentation to determine the cross section channelâs specific energy. This research consisted of two stages. First stage was data collection i.e. sediment sampling, measurement of flow velocity, and measurement of channel dimensions. Second stage was laboratory analysis. Each stage was replicated three times in 2-week intervals. Sediment sampling was done directly on the primary, secondary, and tertiary irrigation channel networks. Sedimentation rate in primary irrigation channel at dry season was 54.99x10-6 tons/day, while at the secondary was 0.88x10-6 tons/day, and at the tertiary was 0.65x10-6 tons/day. Primary channel with channel cross sectional area of 56.734 m2 reduced into 46.541 m2 due to 10.913 m2 area sedimentation. Secondary channel with channel cross sectional area of 3.086 m2 reduced into 2.732 m2 due to 0.354 m2 area of sedimentation. At tertiary channels with channel cross-sectional area of 1.398 m2 reduced into 1.341 m2 due to 0.057 m2 area sedimentation. The rate of sedimentation in the irrigation channel caused changes in the performance of the channel, namely the primary channel; the channel only worked for 76.93%, the secondary channel was 94.2%, and 91.47% in tertiary canals. Keywords: sedimentation, irrigation channel, subsection